Improvement of aerobic energy supply processes in 37-49 yrs old women by means of complex aqua-fitness trainings’ and methodic of endogenous - hypoxic breathing’s application - Furman, Y.M.; Salnikova, S.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: substantiation of purposefulness of complex aqua-fitness training and methodic of endogenous-hypoxic breathing’s application for improvement of women’s functional fitness. Material: in the research 13 women of control group and 12 women of experimental one, who had never trained aqua-fitness earlier, participated. (Their age was 37-49 years old). Results: during 24 weeks, at different stages of the research (after 8, 16 and 24 weeks from the beginning of trainings by the worked out program) we determined indicators of power (maximal oxygen consumption) and capacity (threshold of anaerobic metabolism), which characterize aerobic processes of energy supply. Conclusions: it was proved that complex application of aqua-fitness trainings in combination with methodic of endogenous-hypoxic breathing is effective. It is witnessed by acceleration of increment of absolute and relative indicators of workability, maximal oxygen consumption and threshold of anaerobic metabolism.